Factor influencing customer purchase intention in e-commerce: a study on F.O.S Apparel Sdn Bhd/ Najihah Ismail - Ismail, Najihah (2018)
The importance of e-commerce continues to grow in retail, providing companies with a tool to improve commercial and marketing strategies. The convenience of online shopping rendering it an emerging trend among consumers. This paper examines the interaction between information richness, retailer brand, and extended offers towards customer purchase intention in e-commerce platform used by F.O.S Apparel Sdn. Bhd. In the study, a set of questionnaires were distributed to 250 savvy internet consumers around Klang Valley. The findings revealed that all the variables are positively related to customer purchase intention. However, the interaction effects may differ in these relationships. From the findings of the study, it provide a new idea for future research strategy by adding sufficient factors that can give help to conclude a better results for purchase intention in e-commerce platform.